2021
DOI: 10.1080/03949370.2021.1871967
|View full text |Cite
|
Sign up to set email alerts
|

Not only pigeons: avian olfactory navigation studied by satellite telemetry

Abstract: The olfactory navigation hypothesis proposed to explain homing pigeon navigation predicts that birds learn the association of wind directions and wind-borne odours at home, and once displaced, determine the home direction on the basis of local environmental odours at the release site. This hypothesis was proposed on the basis of two kinds of empirical observations: (i) pigeons develop navigational abilities only if exposed to winds at the home loft, (ii) anosmic pigeons displaced to unfamiliar sites are unable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 100 publications
1
10
0
Order By: Relevance
“…A major hurdle is calculating similar raster surfaces that account for other navigation strategies. For example, another proposed strategy for migratory bird navigation across featureless expanses is olfactory navigation [ 79 ]. It is at present not possible to study olfactory navigation in a modelling approach such as the one presented here, since data on atmospheric concentration of the volatile organic compounds (which are hypothesised to guide the birds) are not available at geographic extents and sufficient spatial and temporal resolutions that would be suitable for analysing long-distance migratory flights.…”
Section: Discussionmentioning
confidence: 99%
“…A major hurdle is calculating similar raster surfaces that account for other navigation strategies. For example, another proposed strategy for migratory bird navigation across featureless expanses is olfactory navigation [ 79 ]. It is at present not possible to study olfactory navigation in a modelling approach such as the one presented here, since data on atmospheric concentration of the volatile organic compounds (which are hypothesised to guide the birds) are not available at geographic extents and sufficient spatial and temporal resolutions that would be suitable for analysing long-distance migratory flights.…”
Section: Discussionmentioning
confidence: 99%
“…The "amazing discovery" -as defined by Wallraff (2015) -of a navigation strategy based on olfaction for the homing pigeon has been put forward by Floriano Papi and co-workers just 50 years ago (see Papi 1989). The evidence that the sense of smell is crucial for the homing behaviour in pigeons and other birds from unfamiliar Foreword sites has been confirmed in recent years, and today the olfactory navigation in birds remains a matter of fact, supported by a large and convincing amount of empirical data (see the contributions of Bonadonna & Gagliardo 2021;.…”
Section: Natale Emilio Baldaccinimentioning
confidence: 93%
“…The amount of information acquired so far has allowed us to make a huge step forward in the understanding of spatial orientation phenomena, especially with the aid of satellite tracking methods, which were largely unavailable until the last decades of the 20th century. This led to a profound change in the methods of field investigation of the homing process and migration phenology of many animal species both vertebrate (see the contributions of Bonadonna & Gagliardo 2021; and even insects such as the butterfly Danaus plexippus and the dragonfly Anax junius (Knight et al 2019). Nevertheless, in the field of bird migratory orientation, some techniques such as the Emlen funnels are still useful not only for passerine but also for other bird species (see Vanni et al 2021).…”
Section: Natale Emilio Baldaccinimentioning
confidence: 99%
“…For many decades, the sense of smell was considered of low relevance in bird biology, and many authors suggested that birds were microsmatic except for some Wallraff et al 1995;Roper 1999;Wallraff 2004;Holland et al 2009;Gagliardo 2013;Gagliardo et al 2013;Wikelski et al 2015;Bonadonna & Gagliardo 2021). Starlings and blue tits use volatile cues to select certain plants to build their nests and those chemical cues seem to be associated with biocidal properties (Clark & Mason 1987;Petit et al 2002).…”
Section: Introductionmentioning
confidence: 99%